2013
DOI: 10.1002/lary.24222
|View full text |Cite
|
Sign up to set email alerts
|

Field of view comparison between two-dimensional and three-dimensional endoscopy

Abstract: N/A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 10 publications
0
29
0
2
Order By: Relevance
“…with the Visionsense© 3-D endoscope improves the depth perception in sinonasal and skull base surgery (28) and may decrease operation times (29), but has a 52 % loss of field e.g. compared to a STORZ 0 0 HD endoscope (30). In my opinion, patients with meningo (encephalo)-celes of the lateral wall of the sphenoidal sinus should be operated by a team of neurosurgeons and ENT surgeons, as is has to be recommended for any form of "(extended) Endoscopic Endosasal surgery" (EES): such pathologies need the combined experience of a (multidisciplinary) skull-base team, as is also expressed by the otolaryngologists (7).…”
mentioning
confidence: 99%
“…with the Visionsense© 3-D endoscope improves the depth perception in sinonasal and skull base surgery (28) and may decrease operation times (29), but has a 52 % loss of field e.g. compared to a STORZ 0 0 HD endoscope (30). In my opinion, patients with meningo (encephalo)-celes of the lateral wall of the sphenoidal sinus should be operated by a team of neurosurgeons and ENT surgeons, as is has to be recommended for any form of "(extended) Endoscopic Endosasal surgery" (EES): such pathologies need the combined experience of a (multidisciplinary) skull-base team, as is also expressed by the otolaryngologists (7).…”
mentioning
confidence: 99%
“…While we have demonstrated that the newer versions of the 3DHD endoscope have a reduction in field of view, this is only modest (2% reduction with endoscope at 2 cm from target and 10.5% with endoscope held at 6 cm from target) (Table ). This compares very favorably to the previous study by Van Gompel et al, which showed a 52% reduction in field of view with a different 3DHD endoscope.…”
Section: Discussionmentioning
confidence: 99%
“…However, the limitations of some previous publications on this subject have been in the selection of experienced surgeons with small numbers. We conducted a study aimed at junior doctors and medical students with little to no endoscopic experience using both objective and subjective measures …”
Section: Introductionmentioning
confidence: 99%
“…When working in a surgical corridor less than a 10-mm opening, this difference is substantial. Next, the field of view with the 3D endoscope is 52% less than conventional 2D endoscopes (7). When working in and around a region with critical neurovascular structures in close proximity, this loss of field of view can potentially result in an increase in iatrogenic injury from the endoscope.…”
Section: -Dimensional (3d) Endoscope Considerationsmentioning
confidence: 99%